Implicit Theories of Intelligence and Achievement Goal Orientations: How are they Associated with College Student Academic Achievement? - Scott C. Marley; M. Jeanne Wilcox (Social Education Research, 2022)
The present study considers social-cognitive theory constructs associated with implicit theories of intelligence and achievement goal theory concerning the academic achievement of first-time college students. We examined growth and entity mindsets along with mastery learning, performance-approach, and performance-avoidance achievement goals in relation to academic achievement. Furthermore, social-cognitive theory predictions were examined to determine whether achievement goals mediated relationships between growth and entity mindsets and academic achievement. We randomly sampled 2,000 college students from a large research-intensive public university in the United States, of whom 839 students provided complete data. Using an online survey, we collected self-reported baseline measures of students' implicit theories of intelligence and achievement goal orientations. We matched data from these measures with two years of college Grade Point Average (GPA). Multiple regression analyses of the baseline data partially supported the hypothesized relationships between growth and entity mindsets with learning and performance goal orientations. A growth mindset was a positive predictor of the mastery learning goal orientation. Unexpectedly, mastery learning positively predicted both performance goal orientations but, relative to entity mindset, was a weaker predictor of performance-avoidance goal orientation. Longitudinal analysis with college GPA as the dependent variable found that growth mindset negatively predicted end-of-year two GPA. This relationship was moderated by mastery goal orientation, with greater levels of mastery goal orientation associated with a larger negative relationship between growth mindset and end-of-year two GPA. Furthermore, the growth mindset by mastery goal orientation by time interaction was statistically significant, with students either high in both or low in both experiencing lower GPA over time. Exploration of the mediation hypotheses was partially supported by path analysis. Implications for theory, practice, and further research are discussed.